2023
DOI: 10.3390/biomedicines11030988
|View full text |Cite
|
Sign up to set email alerts
|

Bacillary Layer Detachment in Neovascular Age-Related Macular Degeneration: Case Series

Abstract: Purpose: This study seeks to report the clinical and multimodal imaging findings of eight eyes of seven patients with neovascular age-related macular degeneration (nAMD) who developed bacillary layer detachment (BALAD). Setting/Venue: The patients were analysed at the Western Eye Hospital in London, UK. Methods: The approaches of this research include clinical examinations and multimodal imaging-based description of cases of nAMD with BALAD. Results: We report multimodal imaging findings of bacillary layer det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…These findings align with results from other similar studies [2,5,8]. While recent reports discussing nAMD with BALAD are limited, existing literature indicates that, in almost all cases, ranibizumab, aflibercept, or bevacizumab rapidly resolved BALAD and significantly improved vision in most patients [2,5,[8][9][10]. Notably, most of these cases involved MNV type 2, similar to our patient's condition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings align with results from other similar studies [2,5,8]. While recent reports discussing nAMD with BALAD are limited, existing literature indicates that, in almost all cases, ranibizumab, aflibercept, or bevacizumab rapidly resolved BALAD and significantly improved vision in most patients [2,5,[8][9][10]. Notably, most of these cases involved MNV type 2, similar to our patient's condition.…”
Section: Discussionsupporting
confidence: 91%
“…There is significant evidence linking type 2 MNV and BALAD [8,9]. Palmieri et al suggested intense exudation and inflammation in certain MNVs might pull on the photoreceptors' myoid, causing a split [10]. Additionally, SRHM observed in this case could be a mix of inflammatory fibrin and photoreceptor debris, potentially contributing to subretinal fibrosis [1,2,5].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…One study [16] aimed to report the clinical and multimodal imaging findings of patients with neovascular AMD who developed bacillary layer detachment (BALAD). This finding is not commonly described in the literature.…”
mentioning
confidence: 99%